2022
DOI: 10.3390/nu14051125
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Deficiency during Pregnancy in Mice Impairs Exercise Performance and Metabolic Function in Adult Offspring

Abstract: Selenium deficiency during the perinatal period programs metabolic dysfunction in offspring. Postnatal exercise may prevent the development of programmed metabolic disease. This study investigated the impact of selenium deficiency on offspring exercise behavior and whether this improved metabolic health. Female C57BL/6 mice were randomly allocated to control (NormalSe, >190 μg/Se/kg, n = 8) or low-selenium (LowSe, <50 μg/Se/kg, n = 8) diets from four weeks before mating. Male offspring were weaned at pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies have reported slight sex-related differences in the progression of metabolic diseases in Se-deficient offspring [38]. These studies focused on the effect of Se deficiency during pregnancy and on the movement of offspring, which differed from the measurement indicators used in this study.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported slight sex-related differences in the progression of metabolic diseases in Se-deficient offspring [38]. These studies focused on the effect of Se deficiency during pregnancy and on the movement of offspring, which differed from the measurement indicators used in this study.…”
Section: Discussionmentioning
confidence: 89%